Strategy for Developing Learning Materials Oriented to Outcomes Based Education Curriculum - Ghofur, Abdul; Polili, Andi Wete; Destiara, Ria Fuji (Budapest International Research and Critics University, 2021)
This study aims to explain the strategy for developing learning materials of Research Methodology courses oriented to O.B.E based curriculum. This study used a qualitative research approach with research and development design. The focus of the research is the process of developing learning materials for Research Methodology courses oriented to O.B.E based curriculum, starting from needs analysis phase to implementation phase. Data were collected using observation techniques. Furthermore, the data were analysed using descriptive narrative technique. Based on the analysis, it is obtained a description that to develop learning materials for Research Methodology courses oriented to O.B.E based curriculum, should carry out the following activities: (1) conduct an analysis of the characteristics and objectives of O.B.E based curriculum and Research Methodology courses, (2) prepare the design of learning materials for Research Methodology courses that are in accordance with the objectives and characteristics of O.B.E based curriculum, (3) develop learning materials, (4) validate learning materials, (5) revise learning materials, and (6) conduct a try out of learning materials. By using this strategy, it can be obtained learning materials for Research Methodology courses that are valid, practical, and effective which can be used to support the implementation of O.B.E based curriculum.